2020
DOI: 10.1007/s10928-020-09698-w
|View full text |Cite
|
Sign up to set email alerts
|

Drug dosing during pregnancy—opportunities for physiologically based pharmacokinetic models

Abstract: Drugs can have harmful effects on the embryo or fetus at any point during pregnancy. Not all the damaging effects of intrauterine exposure to drugs are obvious at birth, some may only manifest later in life. Thus, drugs should be prescribed in pregnancy only if the expected benefit to the mother is thought to be greater than the risk to the fetus. Dosing of drugs during pregnancy is often empirically determined and based upon evidence from studies of nonpregnant subjects, which may lead to suboptimal dosing, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 180 publications
0
50
0
Order By: Relevance
“…A recent review of PBPK models used for pregnant women demonstrated that in a vast majority of cases, only the maternal Cp time profile prediction was investigated, justifying a simplified model structure. Only a few cases were also interested in fetal blood cord exposure [52]. Therefore, as an initial step, a simplified fetal PBPK model was created as data were available to perform multiple validation cases study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of PBPK models used for pregnant women demonstrated that in a vast majority of cases, only the maternal Cp time profile prediction was investigated, justifying a simplified model structure. Only a few cases were also interested in fetal blood cord exposure [52]. Therefore, as an initial step, a simplified fetal PBPK model was created as data were available to perform multiple validation cases study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the metabolic breakdown of sertraline is complicated, and includes CYPs 2B6, 2C9, 2C19, 2D6, and 3A4. The contribution of each isozyme has proven difficult to determine in vivo; however, the variable up‐ or downregulation of CYP isozyme expression during gestation (Abduljalil & Badhan, 2020) may contribute to the disparity observed in some studies (Westin et al., 2017). For example, the approximate 2‐fold decrease in 2C19 activity coupled with approximately 2‐fold increase in 2B6 activity by trimester 3 may negate the overall impact of each pathway, in preference to changes in other physiological factors such as increases in total body water.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Pregnant women are generally not enrolled in trials because of possible risks to the fetus; hence, PBPK offers a unique predictive tool to combine physicochemical and available pharmacokinetic data and gestational-age-dependent changes in patient physiology to quantitively predict the changes in pharmacokinetics of drugs during pregnancy. 23,24 Chaphekar et al describe the physiological changes during pregnancy and how such changes may impact the pharmacokinetics of drugs. 25 In addition, they discuss the application of various PBPK models to not only predict the pharmacokinetics of drugs in various trimesters of pregnancy but also fetal exposures.…”
mentioning
confidence: 99%
“…A multitude of physiological and metabolic changes occur during pregnancy 21,22 . Pregnant women are generally not enrolled in trials because of possible risks to the fetus; hence, PBPK offers a unique predictive tool to combine physicochemical and available pharmacokinetic data and gestational‐age‐dependent changes in patient physiology to quantitively predict the changes in pharmacokinetics of drugs during pregnancy 23,24 . Chaphekar et al describe the physiological changes during pregnancy and how such changes may impact the pharmacokinetics of drugs 25 .…”
mentioning
confidence: 99%